2000
DOI: 10.4049/jimmunol.165.3.1285
|View full text |Cite
|
Sign up to set email alerts
|

The Alloreactive and Self-Restricted CD4+ T Cell Response Directed Against a Single MHC Class II/Peptide Combination

Abstract: The cellular basis for allograft rejection derives from the strong T cell response to cells bearing foreign MHC. While it was originally assumed that alloreactive T cells focus their recognition on the polymorphic residues that differ between syngeneic and allogeneic MHC molecules, studies with MHC class I-restricted CTL have shown that MHC-bound peptides play a critical role in allorecognition. It has been suggested that alloreactive T cells depend more strongly on interactions with the MHC molecule than with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…The 4C T cell has direct allospecificity against I-A d and appears to require an as yet undetermined peptide or peptides, consistent with previous reports showing that the vast majority of direct CD4 ϩ alloreactive responses are peptide dependent (17,18). The 4C T cells respond to an I-A d restricted motif present in skin, heart, and islet allografts (unpublished data).…”
Section: Discussionsupporting
confidence: 85%
“…The 4C T cell has direct allospecificity against I-A d and appears to require an as yet undetermined peptide or peptides, consistent with previous reports showing that the vast majority of direct CD4 ϩ alloreactive responses are peptide dependent (17,18). The 4C T cells respond to an I-A d restricted motif present in skin, heart, and islet allografts (unpublished data).…”
Section: Discussionsupporting
confidence: 85%
“…MLRs were performed as described 17 . Briefly, human ECs and Mφ were cultured on 96-well plates pretreated with the respective stimuli and irradiated.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Such interactions are probably due to the inherent affinity of TCRs for MHC molecules (28,29). Other studies have demonstrated that peptide-specific alloreactive T cells, compared with self-restricted T cells, are more sensitive to peptide stimulation, but interact similarly with MHC/peptide ligands (30).…”
Section: Introductionmentioning
confidence: 99%